# Find the general solution of the given second-order differential equation. y'' + 36y = 0.

**Solution:**

Given equation y'' + 36y = 0.

We know that dy/dx = m

So the given equation becomes m² + 36 =0

m = ± 6i

The roots are conjugate pair (α ± iβ) where α= 0 and β= 6

Let yc be the complementary solution then yc= c₁. e(αˣ).cos(βx) + c₂.e(αˣ).sin(βx)

We know that “e” power zero is equal to 1.

⇒yc= c₁.cos(6x) + c₂.sin(6x)

The general solution is yc= c₁.cos(6x) + c₂.sin(6x)

## Find the general solution of the given second-order differential equation. y'' + 36y = 0.

**Summary:**

The general solution of the given second-order differential equation. y'' + 36y = 0 is y= c₁.cos(6x) +c₂.sin(6x).